Associations Between Self-Reported Sensory Impairment and Risk of Cognitive Decline and Impairment in the Health and Retirement Study Cohort. (12th April 2019) - Maharani, Asri; Dawes, Piers; Nazroo, James; Tampubolon, Gindo; Pendleton, Neil; ,
Abstract: Objectives: We aimed to determine whether self-assessed single (hearing or visual) and dual sensory (hearing and visual) impairments are associated with cognitive decline and incident possible cognitive impairment, no dementia (CIND) and probable dementia. Method: Data were drawn from the 1996–2014 surveys of the Health and Retirement Study (HRS), involving 19, 618 respondents who had no probable dementia and who were aged 50 years or older at the baseline. We used linear mixed models to test the association between self-assessed sensory impairment and cognitive decline followed by a Cox proportional hazard model to estimate the relative risk of incident possible CIND and probable dementia associated with the presence of sensory impairment. Results: Respondents with self-assessed single and dual sensory impairment performed worse in cognitive tests than those without sensory impairment. The fully adjusted incidence of developing possible CIND was 17% higher for respondents with hearing impairment than those without hearing impairment. Respondents with visual impairment had 35% and 25% higher risk for developing possible CIND and probable dementia, respectively, than those without visual impairment. Respondents with dual sensory impairment at baseline were 38% and 26% more likely to develop possible CIND and probable dementia, respectively, than those with no sensory impairment. Discussion: Self-assessed sensory impairment is independently associated with cognitive decline and incident possible CIND and probable dementia. Further studies are needed to identify the mechanism underlying this association and to determine whether treatment of sensory impairment could ameliorate cognitive decline and delay the onset of dementia among older adults.